Self-efficacy and motivation: Improving biology learning outcomes of senior high school students - Firmansyah, Fahmie; Komala, Ratna; Rusdi, Rusdi (Jurnal Pendidikan Biologi Indonesia, 2018)
There are many determining factors influence student learning achievement, including self-efficacy and motivation. The aim of this study was to assess the effect of self-efficacy and motivation on biology learning outcomes. This research was conducted at SSHS 1 of Cilegon city, in which the method used was survey using a quantitative-causal approach aided with path analysis. The sample used were 144 students. The results showed that the path coefficient of self-efficacy towards motivation obtained was 0.596, while the motivation for learning outcomes was 0.600, and self-efficacy toward learning outcomes through motivation was 0.358. These mean that there was a direct effect of self-efficacy towards motivation and motivation towards Biology learning outcomes, whereas indirect effect was possessed by self-efficacy towards Biology learning outcomes through motivation. Thus, teachers should give more attention to studentâs self-efficacy and motivation to inact learning goals.